Early Development of the Mouse Morphome. Issue 3 (May 2016) - Hampel, Joseph A.; Rinkinen, Jacob; Peterson, Jonathan R.; Agarwal, Shailesh; Loder, Shawn; Eboda, Oluwatobi; Enchakalody, Binu; Wang, Stewart C.; Buchman, Steven R.; Levi, Benjamin
Abstract : Introduction: Analytical morphomics focuses on extracting objective and quantifiable data from clinical computed tomography (CT) scans to measure patients' frailty. Studies are currently retrospective in nature; therefore, it would be beneficial to develop animal models for well-controlled, prospective studies. The aim of this study is to develop an in vivo microCT protocol for the longitudinal acquisition of whole-body images suitable for morphomic analyses of bone. Methods: The authors performed phantom studies on 2 microCT systems (Inveon and CT120) to study tissue radiodensity and further characterize system performance for collecting animal data. The authors also describe their design of a phantom-immobilization device using phantoms and an ovariectomized (OVX) mouse. Results: The authors discovered increased consistency along the z-axis for scans acquired on the Inveon compared with CT120, and calibration by individual slice reduces variability. Objects in the field of view had more impact on measurement acquired using the CT120 compared with the Inveon. The authors also found that using the middle 80% of slices for data analysis further decreased variability, on both systems. Moreover, bone-mineral-density calibration using the QCT Pro Mini phantom improved bone-mineral-density estimates across energy spectra, which helped confirm our technique. Comparison of weekly body weights and terminal uterine mass between sham and OVX groups validated our model. Discussion: The authors present a refined microCT protocol to collect reliable and objective data. This data will be used to establish a platform for research animal morphomics that can be used to test hypotheses developed from clinical human morphomics.